2017
DOI: 10.3389/fphys.2017.00923
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of PGC-1α on Fatty Acid Transport across Plasma and Mitochondrial Membranes in the Insulin Sensitive Tissues

Abstract: PGC-1α coactivator plays a decisive role in the maintenance of lipid balance via engagement in numerous metabolic processes (i.e., Krebs cycle, β-oxidation, oxidative phosphorylation and electron transport chain). It constitutes a link between fatty acids import and their complete oxidation or conversion into bioactive fractions through the coordination of both the expression and subcellular relocation of the proteins involved in fatty acid transmembrane movement. Studies on cell lines and/or animal models hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 140 publications
2
35
1
Order By: Relevance
“…We found that the mRNA abundance of PPAR γ was significantly increased by diets supplemented with PGZ or PGZ plus CrMet. However, no report was found on the influence of CrMet on PPAR γ or other lipid metabolism‐related genes, such as PGC‐1 α . Nonetheless, our data showed stable mRNA abundance of PPAR γ and PGC‐1 α with CrMet supplementation, whereas feeding PGZ plus CrMet enhanced PGC‐1 α significantly, and even the individual PGZ improved the PGC‐1 α mRNA abundance by 93.02%.…”
Section: Discussioncontrasting
confidence: 56%
“…We found that the mRNA abundance of PPAR γ was significantly increased by diets supplemented with PGZ or PGZ plus CrMet. However, no report was found on the influence of CrMet on PPAR γ or other lipid metabolism‐related genes, such as PGC‐1 α . Nonetheless, our data showed stable mRNA abundance of PPAR γ and PGC‐1 α with CrMet supplementation, whereas feeding PGZ plus CrMet enhanced PGC‐1 α significantly, and even the individual PGZ improved the PGC‐1 α mRNA abundance by 93.02%.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, PGC-1α is involved in lipid distribution and may upregulate FAT/CD36, FABPpm, and FATP1 mRNA and protein expression in mitochondrial fractions. The latter effect was confirmed solely in murine FAT/CD36 and FABP3 cells [ 14 ].…”
Section: Pgc-1α Can Regulate Lipid Metabolismmentioning
confidence: 90%
“…In literature, it is reported that PPARGC1A may be involved in many biological mechanisms like fatty acid oxidation, glucose utilization, mitochondrial biogenesis, angiogenesis and muscle trophic stimulation [46]. Recent literature [47] demonstrated the role of PPARGC1A in the maintenance of lipid balance via its engagement in numerous metabolic processes related to lipid synthesis and/or lipid utilization ( i . e .…”
Section: Discussionmentioning
confidence: 99%
“…Krebs cycle, β-oxidation, oxidative phosphorylation and electron transport chain). In particular, in insulin-sensitive tissues such as the skeletal muscle, PPARGC1A is regarded as one of the factors eliciting FA uptake by the cells, controlling their oxidation for energy purposes or esterification for the conversion into bioactive fractions [47]. Other regulatory genes up-regulated in LPE compared to L are PRKACA and PRKAR2A , two genes also involved in glucose and lipid homeostasis and in cell growth [48,49].…”
Section: Discussionmentioning
confidence: 99%